Burmannia decurrens (Burmanniaceae): a new record for India - Krishnapriya, M. P; Akhil, M. K.; Harishma, K. H.; Alan, T. S; Krishnaraj, T. P.; Nampy, S. (Rheedea, 2023)
Burmannia decurrens Xiao J.Li & D.X.Zhang, a mycoheterotrophic species recently described from China is reported here as a new addition to the flora of India from Khasi Hills, Meghalaya. A detailed description, photo plate, and notes are provided for easy identification.